Protocol for the safety of brodalumab regarding psychiatric comorbidities in patients with psoriasis - O. Pikou; P. Argitis; A. Karampas; S. Karavia; Z. Chaviaras (European Psychiatry, 2022)
Introduction Brodalumab, an anti-IL17RA monoclonal antibody, is a treatment option for plaque psoriasis related to increased risk of suicidal ideation and behavior, including completed suicide.However, in the literature no causal relationship is reported, and the reported incidence of patients receiving brodalumab that committed suicide did not differ from the expected suicide incidence of the general population.